Evoluç\~ao da política do recolhimento compulsório no Brasil pós-real - Marco A. F. H. Cavalcanti; Christian Vonbun (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– We present a detailed survey of changes in the reserve requirement system in Brazil and analyze the system's main functions and goals during the period from 1994 to 2012. We identify four different subperiods with respect to the use of this policy tool. In the first subperiod, from july 1994 to the end of 1998, reserve requirements were used intensively to stabilize the money supply, credit aggregates and the exchange rate, in the context of strong disinflation and growth of monetization and aggregate demand. In the second subperiod, from 1999 to 2004, the Central Bank used reserve requirements less actively, but still relied on this tool to reinforce the cycles of monetary tightening and easing. During the third subperiod, from 2004 to 2008, changes in the reserve requirement system were little significant and apparently were unrelated to the general objetives of monetary policy. In the fourth subperiod, beginning in 2008, reserve requirements were again used intensively, with the main objective of providing liquidity to the banking system, but also as a tool for aggregate demand management and for selective credit allocation.
Keywords: E31; E40; E42; E50; E51; E52; E53; E58; 330; reserve requirement; monetary policy; macroprudential policy